Lived experiences and coping strategies of people living with Glaucoma in Nigeria: A qualitative study - Affiong Andem Ibanga; Nnaemeka Meribe; Bernadine Nsa Ekpenyong; Kelechukwu Enyinnaya Ahaiwe; Elizabeth Dennis Nkanga; Dennis George Nkanga; Uchechukwu Levi Osuagwu (PLoS ONE, 2025)
Background The diagnosis of visual impairments and other chronic diseases is associated with frustration, anxiety and depression emanating from potential functional limitations, social restrictions, economic burden and future uncertainties. The impact of glaucoma extends across multiple domains of life. This study explores the lived experiences of people with glaucoma to understand the factors that influence their interactions within the community and how they cope with accompanying challenges. Method This study utilised a qualitative research methodology. Data was collected using audio-recorded in-depth semi-structured interviews. Thematic analysis was used to analyse data collected through in-depth interviews. Result Twelve participants aged 22–65 years old, mostly females (58.3%) participated in the study until saturation. Three major themes emerged from the data. The study identified psychosocial reactions to glaucoma diagnosis expressed with unpleasant emotions, fears and concerns about the future by persons living with glaucoma. Glaucoma impacted daily activities, routines and social life resulting in either reduced social activities or they completely stopped socialising. However, engaging in self-motivation and religious activities were useful strategies to cope with these challenges. Other adaptive and coping strategies included following eye care providers’ instructions, attending clinic appointments, making reasonable adjustments at the home and work settings, transferring into accommodation that provides support needs as well as organizing itineraries and activities prior to leaving the house. Conclusion This study provides evidence of the intricate psychosocial impacts of glaucoma, unravelling a spectrum of emotional reactions and lifestyle adaptations. The emotional stress, fears, and disruptions in daily life underscore the profound challenges posed by this chronic eye condition. Self-motivation and religious engagement emerged as potent coping mechanisms, highlighting the importance of psychological and spiritual support. Additionally, the study identifies practical strategies, from adhering to medical instructions to making environmental adjustments, offering valuable insights for healthcare and support networks.